Cost and usage patterns of antibiotics in a tertiary care neurosurgical unit - Manish Singh Sharma; Ashish Suri; Sarat P. Chandra; Shashank S. Kale; Arti Kapil; Bhawani S. Sharma; Ashok K. Mahapatra (Indian Journal of Neurosurgery)
Objectives The routine use of prophylactic antibiotics in neurosurgery has been shown to significantly reduce surgical site infection rates. The documentation of non-surgical site, nosocomial infections in neurosurgical patients remains limited, despite this being a stimulus for prolific antibiotic usage. The actual quantum of antibiotic use in neurosurgery and its role in infection control remain both undocumented and controversial. The authors address this issue with a cost-effectiveness study using historical controls.